The Learning Sciences in Educational Assessment : The Role of Cognitive Models / [electronic resource] - Leighton, Jacqueline P.; Gierl, Mark J. (Cambridge : Cambridge University Press, 2011)
There is mounting hope in the United States that federal legislation in the form of No Child Left Behind will improve educational outcomes. As titanic as the challenge appears to be, however, the solution could be at our fingertips. This volume identifies visual types of cognitive models in reading, science and mathematics for researchers, test developers, school administrators, policy makers and teachers. In the process of identifying these cognitive models, the book also explores methodological or translation issues to consider as decisions are made about how to generate psychologically informative and psychometrically viable large-scale assessments based on the learning sciences. Initiatives to overhaul educational systems in disrepair may begin with national policies, but the success of these policies will hinge on how well stakeholders begin to rethink what is possible with a keystone of the educational system: large-scale assessment.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Educational tests and measurements; Educational psychology; Cognition